PROBLEMATIKA LAYANAN PERPUSTAKAAN KELILING MASA PANDEMI COVID-19 DAN KENORMALAN BARU DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN PADANG PARIAMAN - Atika Hayati Femalinda; Yona Primadesi (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2022)
This study aims to find out the problems of mobile library services at the Padang Pariaman Regency Archives and Library Service during the covid-19 pandemic. This research is a qualitative research with a descriptive approach. There are 2 informants in this study, namely primary informants and secondary informants. The main informants in this study were 5 people with details, two librarians, the Head of the Mobile Library Service Section, the Head of the Library Division, and the Secretary of the Padang Pariaman Regency Archives and Library Service. Data collection techniques were carried out by interview, observation, and documentation methods. This study used validation techniques which included extended participation, persistence of observation and triangulation. The results of this study indicate that services (1) as a result of the covid 19 pandemic mobile libraries cannot operate as they should so that there are several new policies that change mobile library services such as; mobile library services no longer make visits to nagari, currently mobile libraries only go to school as the focus of their services; Mobile library collections can no longer be loaned, but users can only read the collections on the spot. (2) there is no development in the implementation of mobile library services in the new normal. The implementation of mobile library services is still carrying out services like during the pandemic. (3) the need for a solution to the problem of mobile library services during the pandemic delivered by the librarian, namely re-establishing mobile library services to villages and carrying out social inclusion, as well as making changes in library collections.